The Application of Freewriting Techniques in Teaching Writing at Vocational High School Students - Rahmawati, Dwi; Sutiyono, Akhmad; Febriyanti, Febriyanti (Lentera: Jurnal Ilmiah Kependidikan, 2023)
The research aimed to know the effect of Freewriting technique on students’ ability to write procedure text. This research used a quantitative method. There were two classes as the sample in this research which was taken randomly from 24 classes. One class was AKL 1 as experimental, there were 35 students, and the other class was AKL 2 as the control class, there were 35 students. In determining the sample, the researcher used cluster random sampling technique. In collecting the data, the researcher used a writing test. In analysing the data, the researcher used the t-test formula. Based on the data analysis, it can be concluded that ttest 6.66 and ttable = 1.67 with the significance 5% (0,05) and ttable =2.39 with the significance 1% (0,01). It means that ttest > ttable. So, Ha was accepted. This shows that there is any positive and significant influence of using freewriting technique on the students’ writing ability. The students who were taught through the Freewriting technique got a higher score than those who were not taught through Freewriting technique. The average score of the experimental class was 68.61 and the average score of the control class was 57.14.